Papers - New York Meeting – February, 1929 - Relation of Nitrogen to Blue Heat Phenomena in Iron and Dispersion Hardening in the System Iron-nitrogen - R. S. Dean; R. O. Day (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
In constructing a theory of the flow and hardening of metals, v necessarily make use of such phenomena as seem to be universal1 observed in metals. It is, therefore, a matter of concern to the con structors of such mnemonic systems if one or two of the group classific as metals show anomalous behavior. Such egregious phenomena observed in pure or nearly pure iron in the reaction of its mechanic properties to low-temperature annealing after cold work and to increase temperature of testing. In short it has been generally observcd tha iron, as an outstanding exception among metals, increases its hardnes and strength by low-temperature annealing after cold work,' and alt by increase of testing temperature to the range of 150" to 300" C. The investigation here recorded was made then with the object ( ascertaining if similar phenomena were observed in high-purity iro and, if not, to the presence of which impurities these phenomena coul be traced. Experimental Procedure Three kinds of iron were taken for a study of hardening by rehcatin after cold work: 1. Vacuum-melted electrolytic iron; melted in an Arsem furnace in a magnesia crucible. That this iron was of high purity is indicated b a magnetic permeability above 20,000. 2. Electrolytic iron melted in air in a small laboratory furnace. 3. Armco iron, commercial material. These materials in the form of forged bars, annealed at 980" C. in vacuum, were reduced 30 per cent. in thickness by cold rolling and the reheated to temperatures varying from 100' to 500' C. The Rockwe hardness number was measured after each treatment. The results and shown in Fig. 1, curves 1, 2 and 3.